PENERAPAN TANAMAN HIDROPONIK DARI BOTOL BEKAS DI DESA PONDOK MAKMUR KECAMATAN AIR MANJUTO KABUPATEN MUKOMUKO, BENGKULU - Ferry Lismanto Syaiful; Wiranda Erza Pratama (LPPM Universitas Andalas, 2021)
One of the excellent farming techniques for cost and straightforward application is the hydroponic farming technique. Hydroponics is the cultivation of plants/agriculture without using soil as a substitute for soil, namely water as a planting medium and supporting plant growth. The objectives of this activity are 1. to provide knowledge about hydroponic farming techniques, 2. to provide an understanding of the utilization of waste such as used bottles to make simple hydroponics, and 3. to provide an understanding of the business opportunities obtained from making simple hydroponics. This activity was carried out in Pondok Makmur Village, Air Manjuto District, Muko-muko Regency, Bengkulu Province. The target of the activity is the community of Pondok Makmur Village, Air Manjuto District, Mukomuko Regency, Bengkulu Province. The methods used in this activity are socialization, demonstration of making simple hydroponics from used bottles, and discussions. Based on the results of the activities that have been carried out, there has been a good response from the activity participants. Although some of the participants were not familiar with hydroponic plant cultivation using these used bottles. After participating in the activity, it was seen that there was an increase in public knowledge about hydroponic farming techniques using used bottles as planting media. Then the implementation of this activity was seen to increase the skills and abilities of the community in utilizing used bottles in hydroponics. Besides that, the community also understands the business opportunities obtained from making simple hydroponics from used bottles. This farming technique with a simple hydroponic system is an alternative to gardening activities that are easier to implement, do not require much money, and are easy to maintain for the community.